2022
DOI: 10.3390/insects13121112
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes and COI Gene Sequences of Chironomus sp. Le1 (Kiknadze and Salova, 1996), Ch. laetus (Belyanina and Filinkova, 1996) and Their Hybrid from the Yamal Peninsula, Arctic Zone of Russia

Abstract: The study of the biological diversity of the Arctic zone yields intriguing results. Initial research on the lakes of the Yamal Peninsula resulted in the identification of Chironomus laetus and the hybrid Ch. laetus x Ch. sp. Le1. To avoid misidentification, we used morphological, cytogenetic, and molecular genetic approaches. By cytogenetics, in Ch. sp. Le1, seven banding sequences were found: Le1A1, Le1B1, Le1C1, Le1D1, Le1E1, Le1F1, and Le1G1. The karyotype of Ch. laetus was mapped for the first time; it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Another explanation is interspecific hybridization and horizontal transfer of mitochondrial genes with fixation in one of the initial species in a population ( Guryev and Blinov 2002 ; Polukonova et al 2009 ; Karmokov 2019 ; Bolshakov et al 2021 ). Previously, we confirmed the existence of hybrids even between species from different cytocomplexes ( Bolshakov et al 2022b ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Another explanation is interspecific hybridization and horizontal transfer of mitochondrial genes with fixation in one of the initial species in a population ( Guryev and Blinov 2002 ; Polukonova et al 2009 ; Karmokov 2019 ; Bolshakov et al 2021 ). Previously, we confirmed the existence of hybrids even between species from different cytocomplexes ( Bolshakov et al 2022b ).…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, we did not have the opportunity to collect more samples of this species. We regularly suggest to use a comprehensive approach to the species identification of the genus Chironomus , which includes morphology, cytogenetics and molecular genetics ( Bolshakov and Movergoz 2022 ; Bolshakov et al 2022a , 2022b ). In this study, we have decided to use a single Chironomus larva to obtain a complex of scientific data.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the length of 535 bp is insufficient for an accurate identification of the sequence of C. bernensis (JN016851), or it could be a result of interspecific hybridization and horizontal transfer of mitochondrial genes, with fixation in one of the parental species in the population [37,54,55]. We have already shown that hybridization of species from different cytocomplexes is possible [56]. Sample C. muratensis (KC250748) from Sweden may also be misidentified.…”
Section: Discussionmentioning
confidence: 99%